SiC substrate with uniform stress distribution in three-dimensional direction and SiC crystal
The SiC substrate and crystal with uniform stress distribution address defects and mechanical stress issues by layering and using a TaC coating, enhancing quality and usability, and facilitating high-quality epitaxial growth.
Patent Information
- Application Number
- CN202310746123.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-21
AI Technical Summary
SiC crystals and substrates suffer from non-uniform stress distribution and mechanical processing-induced defects, leading to reduced quality, increased defects in epitaxial layers, and limited usability due to inherited stress during crystal growth and processing.
A SiC substrate and crystal with uniform stress distribution in three-dimensional directions are achieved by dividing the substrate into layers with controlled radial and axial stress differences, using a method that includes precise thickness and stress range specifications, and employing a TaC coating with through-holes to improve temperature uniformity during crystal growth.
The uniform stress distribution enhances substrate quality, expands its use scope, improves epitaxial layer growth, and reduces defects, while the TaC coating aids in producing high-quality SiC crystals with reduced internal stress.
Smart Images

Figure CN119177489A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a SiC substrate and a SiC crystal with uniform stress distribution in three-dimensional directions, and belongs to the technical field of SiC production and processing. Background Art
[0002] During the growth process of SiC crystals, various defects such as polycrystalline, polymorphic, micropipes, dislocations, etc. are easily introduced into the crystals due to the imbalance of Si / C ratio, the introduction of impurities and temperature gradient changes. The defects will cause lattice distortion. More seriously, the crystal form will change, such as the generation of 4H, 6H, 3C, 15R and other polymorphic symbiosis. The lattice distortion releases stress by generating defects, that is, introducing internal stress into SiC, thereby reducing the quality of SiC crystals, limiting the scope of use of crystals, affecting the subsequent processing of SiC crystals, and reducing the yield rate of products.
[0003] On the other hand, during the processing of SiC substrates, most of them are obtained by cutting from crystal rods through mechanical processing, such as laser cutting, wire cutting, etc., and then surface treatment is performed through mechanical processing such as grinding and polishing. During the substrate processing, mechanical stress will cause microcracks on the surface, thereby introducing a damaged layer. For SiC, the difference in the thickness of the damage layer on the C and Si surfaces will affect the surface quality of the substrate, thereby affecting the production and processing of downstream products. Therefore, there are both internal stress and surface stress in the SiC substrate. When the SiC substrate is used for crystal growth or epitaxial layer growth, the stress of the SiC substrate will be inherited to the crystal or epitaxial layer, resulting in an increase in epitaxial layer and crystal defects, easy cracking and uneven quality, making it difficult to carry out subsequent processing and production. Summary of the invention
[0004] In order to solve the above problems, a SiC substrate and a SiC crystal with uniform stress distribution in three-dimensional directions are provided. The SiC substrate is divided into a first surface layer, a second surface layer and an intermediate layer. The radial stress in the SiC substrate in the first surface layer, the second surface layer and the intermediate layer is relatively low, and the stress distribution uniformity between the layers is good, which can improve the quality of the SiC substrate, expand the scope of use of the SiC substrate, and is beneficial to the production and processing of downstream products. When it is used for crystal or epitaxial layer growth, the quality of the crystal and the epitaxial layer can be improved.
[0005] According to one aspect of the present application, a SiC substrate with uniform stress distribution in three-dimensional direction is provided, wherein the thickness of the SiC substrate is not less than 100 μm, and the SiC substrate comprises a first main surface and a second main surface, wherein the area of the first main surface facing the second main surface at 10 nm to 30 μm is a first surface layer, and the area of the second main surface facing the first main surface at 10 nm to 30 μm is a second surface layer, and the first surface layer and the second surface layer are between an intermediate layer;
[0006] On the same axis, at any plane parallel to the first main surface or the second main surface, Smax1 represents the maximum absolute value of radial stress in the first surface layer, Smax2 represents the maximum absolute value of radial stress in the middle layer, Smax3 represents the maximum absolute value of radial stress in the second surface layer, △S1=Smax2-Smax1, △S2=Smax2-Smax3, -15MPa≤△S1≤10MPa, -15MPa≤△S2≤10MPa;
[0007] Preferably, -14.9MPa≤△S1≤7.7MPa, -14.6MPa≤△S2≤7.9MPa.
[0008] The above △S1 represents the difference in radial stress between the first surface layer and the middle layer, and △S2 represents the difference in radial stress between the second surface layer and the middle layer. The closer the △S1 value is to 0, the better the uniformity of radial stress distribution of the first surface layer and the middle layer, and the better the quality of the substrate. The closer the △S2 value is to 0, the better the uniformity of radial stress distribution of the second surface layer and the middle layer, and the better the quality of the substrate. If both △S1 and △S2 are close to 0 at the same time, it means that the radial stress distribution of the substrate is uniform in the entire axial direction, and the quality of the substrate is optimal.
[0009] Optionally, at any plane parallel to the first main surface in the first surface layer, the radial stress of the SiC substrate is -15 MPa to 15 MPa, and at any plane parallel to the second main surface in the second surface layer, the radial stress of the SiC substrate is -15 MPa to 15 MPa;
[0010] At any plane in the intermediate layer parallel to the first main surface or the second main surface, the radial stress of the SiC substrate is -10 MPa to 10 MPa.
[0011] Since the SiC substrate is subjected to tensile and compressive stresses, the interplanar spacing d undergoes corresponding expansion and contraction changes. Therefore, when using Raman to test stress, the Raman peak intensity will move to low frequency or high frequency. When the substrate is subjected to tensile stress, the Raman peak shifts to low frequency, and the obtained stress value is positive. When the substrate is subjected to compressive stress, the Raman peak shifts to high frequency, and the obtained stress value is negative. Therefore, the positive and negative before the stress value in this application represent the force direction inside the substrate, and the absolute value of the value represents the magnitude of the stress. For example, when the radial stress in the first surface layer of the SiC substrate is -15MPa and the radial stress in the second surface layer is -10MPa, it means that the radial stress in the first surface layer and the second surface layer is compressive stress, and the radial pressure of the first surface layer is greater than the radial pressure of the second surface layer.
[0012] The first surface layer and the second surface layer are the surface stress of the substrate. The thickness of the first surface layer and the second surface layer varies with the processing technology of substrate cutting, grinding and polishing. The thinner the thickness of the first surface layer and the second surface layer, the smaller the radial stress of the first surface layer and the second surface layer. The area of 10nm to 30μm from the first main surface to the second main surface is the first surface layer. When the value of the above area is closer to 10nm, the radial stress of the SiC substrate in the first surface layer is smaller, that is, closer to 0MPa. When the value of the above area is closer to 30μm, the radial stress of the SiC substrate in the first surface layer is greater, that is, closer to -15MPa or 15MPa. Similarly, the area of 10nm to 30μm from the second main surface to the first main surface is the second surface layer. When the value of the above area is closer to 10nm, the radial stress of the SiC substrate in the second surface layer is smaller, that is, closer to 0MPa. When the value of the above area is closer to 30μm, the radial stress of the SiC substrate in the second surface layer is greater, that is, closer to -15MPa or 15MPa.
[0013] Preferably, -5MPa≤Smax3-Smax1≤5MPa, more preferably, -4.9MPa≤Smax3-Smax1≤5MPa. Smax3-Smax1 represents the difference in radial stress between the first surface layer and the second surface layer. The smaller the value, the better the uniformity of radial stress distribution between the first surface layer and the second surface layer of the substrate.
[0014] Optionally, the diameter of the SiC substrate is greater than 150 mm, preferably greater than 200 mm.
[0015] Optionally, the radial stress includes radial absolute stress and radial relative stress;
[0016] At any plane parallel to the first main surface in the first surface layer, the radial absolute stress of the SiC substrate is -15 MPa to 15 MPa, and the radial relative stress of the SiC substrate is -15 MPa to 14.5 MPa, preferably -14.9 MPa to 14.5 MPa;
[0017] At any plane parallel to the second main surface in the second surface layer, the radial absolute stress of the SiC substrate is -15 MPa to 15 MPa, and the radial relative stress of the SiC substrate is -15 MPa to 14.5 MPa, preferably -14.7 MPa to 14.5 MPa;
[0018] At any plane in the intermediate layer parallel to the first main surface or the second main surface, the radial absolute stress of the SiC substrate is -10 MPa to 10 MPa, and the radial relative stress of the SiC substrate is -8 MPa to 8 MPa.
[0019] Absolute stress can reflect the difference between the substrate and the perfect SiC crystal without defects, and is used to determine the stress level of the SiC substrate. However, since it is difficult to achieve a perfect SiC substrate with current technology, the relative stress can be used to determine the relative stress distribution within the substrate surface.
[0020] For example, when the absolute stress of the substrate is large and the relative stress is small, it means that there are more in-plane defects, but the stress distribution is uniform, the crystal quality is poor, and the uniformity quality in each area of the substrate is poor; if the absolute stress is small and the relative stress is large, the overall substrate quality is good, but there are abnormal quality deviations in some areas.
[0021] The reference value of absolute stress in this application is the reference stress calculated based on the standard Raman peak position obtained according to the perfect lattice parameters of SiC, which is marked as 0; the relative stress is to take a reference value on the entire test plane, and the value of each test point is related to the reference value for numerical calculation to obtain the relative stress value of the test point, and the reference value includes but is not limited to the average value, median, mode and any one of the results calculated by other statistical functions of all stress values on the entire test plane.
[0022] Optionally, on the same axis, at any plane parallel to the first main surface or the second main surface, Smin1 represents the minimum absolute value of radial stress in the first surface layer, Smin2 represents the minimum absolute value of radial stress in the middle layer, Smin3 represents the minimum absolute value of radial stress in the second surface layer, △S3=Smin2-Smin1, △S4=Smin2-Smin3, -5MPa≤△S3≤5MPa, -5MPa≤△S4≤5MPa;
[0023] Preferably, -5MPa≤Smin3-Smin1≤5MPa.
[0024] More preferably, -4.8MPa≤ΔS3≤5MPa, -5MPa≤ΔS4≤4.8MPa, -4.5MPa≤Smin3-Smin1≤4.4MPa
[0025] Optionally, an axial test is performed vertically extending into the SiC substrate from any point of the first main surface, and the axial stress of the SiC substrate in the first surface layer is -10MPa to 10MPa, the axial stress of the SiC substrate in the middle layer is -10MPa to 10MPa, and the axial stress of the SiC substrate in the second surface layer is -10MPa to 10MPa.
[0026] Optionally, the axial stress includes an axial absolute stress and an axial relative stress, and is tested axially by extending vertically from any point of the first main surface into the SiC substrate;
[0027] The axial absolute stress of the SiC substrate in the first surface layer is -10 MPa to 10 MPa, and the axial relative stress of the SiC substrate in the first surface layer is -8 MPa to 8 MPa, preferably -7.8 MPa to 7.9 MPa;
[0028] The axial absolute stress of the SiC substrate in the intermediate layer is -10 MPa to 10 MPa, and the axial relative stress of the SiC substrate in the intermediate layer is -8 MPa to 8 MPa, preferably -8.0 MPa to 7.8 MPa;
[0029] The axial absolute stress of the SiC substrate in the second surface layer is -10 MPa to 10 MPa, and the axial relative stress of the SiC substrate in the second surface layer is -8 MPa to 8 MPa, preferably -7.8 MPa to 8.0 MPa.
[0030] Optionally, an axial test is performed vertically extending from any point of the first main surface into the SiC substrate, S1 is recorded as the maximum axial stress in the first surface layer, S2 is recorded as the minimum axial stress in the first surface layer, △S5=S1-S2, 0MPa≤△S5≤15MPa;
[0031] S3 is recorded as the maximum axial stress in the middle layer, S4 is recorded as the minimum axial stress in the middle layer, △S6 = S3-S4, 0MPa≤△S6≤10MPa;
[0032] S5 is recorded as the maximum axial stress in the second surface layer, S6 is recorded as the minimum axial stress in the second surface layer, △S7=S5-S6, 0MPa≤△S7≤15MPa.
[0033] The above-mentioned maximum axial stress and minimum axial stress refer to the true values of the axial stress, which distinguish between compressive stress and tensile stress in the axial direction. For example, on any axis, the comprehensive axial stress of the middle layer is -5-1MPa, then the maximum axial stress is 1MPa, the minimum axial stress is -5MPa, and △S6 is 6MPa. △S5, △S6 and △S7 represent the degree of change in the axial crystal plane spacing of the first surface layer, the middle layer and the second surface layer of the substrate at the microscopic level. The smaller the above-mentioned △S5, △S6 and △S7 are, the smaller the change in the axial crystal plane spacing of the substrate is.
[0034] Preferably, 0MPa≤△S5≤14.9MPa, 0MPa≤△S7≤14.3MPa.
[0035] Optionally, the crystal form of the SiC substrate is one of 2H-SiC, 4H-SiC, 6H-SiC, 3C-SiC, and 15R-SiC, preferably 4H-SiC.
[0036] Optionally, the SiC substrate is a semi-insulating SiC substrate or a conductive SiC substrate.
[0037] Optionally, the curvature of the SiC substrate is -100 μm to 100 μm, preferably -50 μm to 50 μm, and more preferably -11 μm to 15 μm.
[0038] Preferably, an off angle of the first main surface and / or the second main surface relative to the {0001} plane is less than 4°.
[0039] According to another aspect of the present application, a SiC crystal with uniform stress distribution in three-dimensional directions is provided, wherein the thickness of the SiC crystal is not less than 0.35 mm, and the SiC crystal includes an upper surface and a lower surface. In the region from the upper surface to the lower surface, the radial stress at any horizontal plane is -10 MPa to 10 MPa.
[0040] Preferably, the diameter of the SiC crystal is greater than 150 mm, preferably greater than 200 mm.
[0041] Optionally, an axial test is performed extending downward from any point on the upper surface of the SiC crystal, and the axial stress of the SiC crystal is -10 MPa to 10 MPa.
[0042] Preferably, the axial stress includes axial absolute stress and axial relative stress;
[0043] An axial test is performed by extending downward from any point on the upper surface of the SiC crystal. The axial absolute stress of the SiC crystal is -10 MPa to 10 MPa, and the axial relative stress of the SiC crystal is -8 MPa to 8 MPa, preferably -8 MPa to 7.8 MPa.
[0044] Optionally, the radial stress includes radial absolute stress and radial relative stress;
[0045] In the region from the upper surface to the lower surface, the radial absolute stress at any horizontal plane of the SiC crystal is -10 MPa to 10 MPa, and the radial relative stress at any horizontal plane of the SiC crystal is -8 MPa to 8 MPa.
[0046] The above absolute stress and relative stress can reflect the same characteristics as the substrate absolute stress and relative stress.
[0047] Optionally, an axial test is performed extending downward from any point on the upper surface of the SiC crystal, S7 is recorded as the maximum axial stress of the SiC crystal, S8 is recorded as the minimum axial stress of the SiC crystal, △S8=S7-S8, 0MPa≤△S8≤10MPa.
[0048] The above-mentioned maximum axial stress and minimum axial stress refer to the true value of the axial stress, which distinguishes between compressive stress and tensile stress in the axial direction. For example, on any axis, the axial stress of the SiC crystal is -5MPa~5MPa, then the maximum axial stress is 5MPa, the minimum axial stress is -5MPa, and △S8 is 10MPa. The △S8 represents the degree of change in the axial interplanar spacing of the crystal. The smaller the △S8, the smaller the change in the axial interplanar spacing of the crystal.
[0049] Preferably, 0MPa≤△S8≤6.3MPa, more preferably, 0MPa≤△S8≤1.1MPa.
[0050] According to another aspect of the present application, a method for preparing a SiC single crystal is provided, comprising the following steps:
[0051] (1) Adding silicon carbide powder into a graphite crucible;
[0052] (2) Evacuate the furnace to 10 -6 mbar, and then introduce high-purity inert gas to 300-500mbar, repeat this process 2-3 times, and finally evacuate the furnace to 10 -6 Below mbar;
[0053] (3) introducing high-purity inert gas into the furnace body, raising the pressure to 10-100 mbar within 1-3 hours, and continuously introducing high-purity inert gas and maintaining the pressure constant;
[0054] (4) Crystal growth stage: While maintaining the pressure unchanged, the temperature inside the furnace is raised to the crystal growth temperature of 2200K-2800K within 3-5 hours, and the growth time is 30-150 hours;
[0055] (5) After the crystal growth is completed, open the furnace body and take out the graphite crucible to obtain the SiC crystal.
[0056] Optionally, the graphite crucible is coated with a TaC coating, the TaC coating is deposited on the surface of the graphite substrate, and the TaC coating is uniformly distributed with through-holes, and the density of the through-holes is 160-310 / mm 2 The TaC coating contains through-holes, which can improve the transmission rate of the silicon carbide raw material atmosphere and the uniformity of the temperature field during crystal growth, thereby increasing the growth rate of the crystal and reducing the internal stress of the crystal, thereby obtaining a high-quality and low-stress silicon carbide crystal.
[0057] Optionally, the aperture of the through-type through hole is 2-7 μm, preferably 2.3-6.1 μm. This aperture can improve the transmission rate of the silicon carbide raw material atmosphere without reducing the protection performance of the graphite substrate, avoid the crystal from being squeezed by the thermal expansion of the graphite substrate in the thermal field to generate edge stress, and further reduce the stress in the crystal.
[0058] Optionally, the thickness of the TaC coating is 30-400 μm, the TaC grains in the TaC coating are arranged in a stacking staggered manner, and the size of the TaC grains is 15-50 μm. The TaC grains in the TaC coating are oriented and grow along the
[200] and
[220] directions. The growth direction of the TaC grains can improve the temperature resistance and thermal chemical corrosion resistance of the TaC coating, thereby reducing the interference of the graphite substrate on the crystal growth environment and improving the stability of the crystal environment.
[0059] The beneficial effects of this application include but are not limited to:
[0060] 1. The stress introduced by temperature gradient changes or crystal growth environment changes during SiC crystal growth is the stress in the middle layer of the SiC substrate. The stress in the first surface layer and the second surface layer of the SiC substrate is the stress generated during the processing of the SiC crystal into the SiC substrate. The stress distribution in the first surface layer, the second surface layer and the middle layer of the SiC substrate of the present application is uniform and the stress value is very low, which proves that the quality of the SiC substrate is good and is conducive to the production and processing of downstream products.
[0061] 2. The present application tests the stress of the SiC substrate quantitatively and distinguishes between the surface stress and the internal stress in the SiC substrate. It can control the stress distribution of the SiC substrate within a reasonable range according to the different downstream products for which the SiC substrate is used to prepare, so as to expand the scope of use of the SiC substrate.
[0062] 3. According to the SiC substrate of the present application, the stress distribution in the three-dimensional direction is uniform in the first surface layer, the second surface layer and the middle layer, which proves that the SiC substrate can be regarded as a stress-uniform body and the surface shape of the SiC substrate is also improved.
[0063] 4. The present application utilizes a TaC coating with through-type through holes formed on the surface of the crucible, which can ensure the transmission of the raw material atmosphere during crystal growth while improving the uniformity of the temperature field, so that it can be used to prepare low-stress silicon carbide crystals. The substrate prepared from the crystal can improve the growth quality of epitaxial wafers and subsequent crystals.
[0064] 5. According to the distribution of stress in each layer of the SiC substrate of the present application, the parameters of each process of crystal growth and / or substrate processing can be adjusted to prepare a high-quality SiC substrate, and through the quantitative testing method of the present application, the detected stress also includes the stress in the substrate that has not been released through defects due to lattice distortion, thereby improving the detection accuracy of stress in the SiC substrate and reflecting the entire stress information of the entire SiC substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0066] Figure 1 This is a flow chart of the Raman stress test involved in Example 1 of the present application.
[0067] Figure 2 This is the axial peak intensity distribution diagram of the 4H-SiC substrate involved in Example 2 of the present application.
[0068] Figure 3 This is a schematic diagram and stress axial distribution diagram of the Raman axial test SiC substrate involved in Example 3 of the present application.
[0069] Figure 4 This is a morphology characterization diagram of the TaC coating in crucible 1# involved in Example 6 of the present application.
[0070] Figure 5 This is the XRD test diagram of the TaC coating and TaC in crucible 1# in Example 6 of the present application. DETAILED DESCRIPTION
[0071] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0072] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0073] The principle of using Raman to test the stress of the substrate in the following embodiments is as follows: the Raman spectrometer passes a monochromatic laser of a certain wavelength through a series of optical paths and then converges the laser through an objective lens to irradiate the substrate surface, and the laser photons interact with the substrate lattice to cause photon scattering. The occurrence of Raman scattering is related to the lattice vibration of the substrate itself. When there is residual stress in the sample, the tensile and compressive stresses will cause the atomic bond length to be elongated or shortened accordingly, thereby causing the atomic vibration frequency to decrease or increase, which is reflected in the Raman spectrum as the characteristic peak of the substrate moves to a low frequency or a high frequency, that is, a peak position offset occurs.
[0074] Example 1 Quantitative Testing Method for Substrate Stress
[0075] (1) Calculation of peak position shift and stress conversion coefficient
[0076] First, a single crystal XRD diffractometer is used to test the silicon carbide substrate and the substrate is analyzed according to the reciprocal lattice space. The parameters of the standard 4H-SiC substrate are calculated and compared with the standard parameters. Then, according to the Bragg diffraction equation: 2dsinθ=nλ, where d is the interplanar spacing, θ is the diffraction half-angle, n is the diffraction order, and λ is the wavelength, the θ and d of different substrates are tested. It can be seen that the tensile and compressive stress inside the crystal causes the interplanar spacing d to expand and contract accordingly. According to the different interplanar spacings d0 and d x , d x It is divided into d1 and d2, where d0 is the theoretical crystal plane spacing, d1 is the crystal plane spacing after tensile stress, and d1 is greater than d0, and d2 is the crystal plane spacing after compressive stress, and d2 is less than d0. The difference in crystal plane spacing △d at different positions is calculated, △d=d1-d0 or △d=d0-d2.
[0077] The actual peak position of the substrate is obtained according to the Raman test, and the peak position offset △v at different test points is calculated compared with the standard peak position; the stress value σ of the silicon carbide substrate at different test points is calculated in combination with Hooke's law or stress-strain formula, and the ratio of the peak position offset to the stress value at different test points is the peak position offset and stress conversion coefficient μ, which ranges from -125 to -2500.
[0078] The calculation formula of Hooke's law is σ / S=E×(△d / d0), where S is the area affected by σ, which is a fixed value. When Hooke's law is applicable to microscopic calculations, S is the microscopic area, which can be calculated as unit 1. E is the Young's modulus of the substrate, which is a fixed parameter of the substrate. △d is the difference in crystal plane spacing at different positions, d0 is the theoretical crystal plane spacing, and σ is the stress value that needs to be calculated.
[0079] The calculation formula for stress and strain is σ=E×△d, where E is the Young's modulus of the substrate, which is a fixed parameter of the substrate, △d is the difference in crystal plane spacing at different positions, and σ is the stress value to be calculated.
[0080] (2) Quantitative test method of substrate stress
[0081] refer to Figure 1 First, set the Raman test points. You can perform single-point testing or Mapping scanning on the entire substrate. Therefore, single-point testing is a sporadic coordinate point setting, and Mapping scanning is 10x10~50x50 and more points. You can choose the appropriate test method according to the properties of the substrate to determine the Raman test coordinates of the silicon carbide substrate.
[0082] The test results are then output, including but not limited to editable peak position, peak intensity data and Mapping.
[0083] The output data is then subjected to peak position fitting, where fitting functions include but are not limited to Gaussian, Lorentz, GaussLor, AGauss, Aloren and AGaussLor, to obtain precise peak position values and peak position offsets, with the peak position accurate to more than one decimal place.
[0084] Finally, according to the peak shift and stress conversion coefficient μ calculated in (1) and the peak shift △v obtained in the Raman test, the stress value of silicon carbide is calculated as follows: σ(MPa)=μ×△v(cm -1 ), and finally output the stress test image of the substrate.
[0085] Example 2: Test of curvature of substrate surface
[0086] Since SiC is subjected to a lot of external mechanical stress during the process of preparing wafers from crystals through a series of processes, it is difficult to ensure that the surface is completely level, that is, there is a certain degree of curvature. In order to eliminate the influence of substrate surface curvature on substrate surface stress and internal stress test, it is necessary to first perform a curvature test on the substrate. According to the curvature, the substrate surface stress is tested with equal spacing focus, and the substrate internal stress is tested with equal spacing focus or equal focus plane.
[0087] After the curvature test, the tester needs to be calibrated using single crystal silicon. First, a Z-axis mapping test is performed on the single crystal Si to confirm that it is a Gaussian distribution. The surface of the single crystal Si substrate is taken as the zero point, and an axial mapping test is performed from -100μm inside the single crystal Si substrate to +20μm above the single crystal Si substrate to analyze the change in Raman signal intensity and the axial peak intensity distribution diagram of the single crystal Si substrate. The single crystal Si substrate is a non-transparent material, so its peak intensity presents a Gaussian distribution, with the surface zero point position as the symmetry axis; then a surface focusing single point test is performed on the single crystal Si, and the single crystal Si Raman peak position is made to be 520.70cm through the correction instrument. -1 , at this time, it means that the instrument optical path has been calibrated.
[0088] The 4H-SiC substrate was tested in the Z direction using the calibrated tester. The Raman laser was transmitted from -100μm inside the 4H-SiC substrate to +20μm above the 4H-SiC substrate. Figure 2This is the axial peak intensity distribution diagram of the 4H-SiC substrate. The 4H-SiC substrate and other silicon carbide are transparent materials, so the Raman laser can penetrate into the silicon carbide substrate, and as the Raman laser penetration depth increases, the feedback signal gradually weakens. Other silicon carbides include semi-insulating, conductive, and 3C, 4H, 15R, 6H and other silicon carbide substrates with different crystal forms. Therefore, the Raman peak intensity of the silicon carbide substrate gradually decreases as the Raman laser penetrates deeper into the silicon carbide substrate.
[0089] The Raman device’s autofocus function can be used to automatically find the strongest peak of the test signal on the substrate surface, so that the curvature of the substrate surface can be measured with the help of this function. The specific method is as follows:
[0090] S1: First, ensure that the test platform is level, select a fixed origin (0,0) on the test platform, and mark the point as the three-dimensional coordinate (0,0,0);
[0091] S2: Raise the objective lens to a height that does not touch the substrate according to the thickness of the substrate, and automatically focus on any point on the substrate surface where the test signal is the strongest. Mark this position as (a, b, c), then adjust the Raman laser downward by a distance of H and focus on the position to (a, b, cH);
[0092] S3: Adjust the Raman laser test position to (0,0, cH) to perform an iso-focal plane test to obtain a two-dimensional peak intensity scan of the substrate surface. Figure 2 The peak intensity distribution relationship of the silicon carbide substrate in the middle can be used to obtain the distance between the focusing plane of the Raman laser and the surface of the silicon carbide substrate, thereby obtaining the in-plane curvature of the substrate and outputting the in-plane curvature distribution map of the substrate.
[0093] Example 3 Axial test distinguishes substrate surface stress from internal stress
[0094] Since the substrate is affected by the temperature field and the introduction of inclusions during the crystal growth process, thermal stress and residual stress exist inside the crystal, and the substrate is obtained after a series of cutting, grinding and polishing. The above-mentioned processing process of the crystal to form the substrate will cause surface lattice distortion, thereby generating surface stress. In order to further distinguish the surface stress from the body stress of the substrate, the substrate is subjected to axial testing according to the light transmittance characteristics of silicon carbide, namely, Z-direction Mapping, with the substrate surface as the zero point. The test range of the axial test is from -150μm to -30μm inside the substrate to above the substrate surface.
[0095] Test schematic diagram Figure 3As shown in (a), the laser spot is gradually focused upward from the substrate body to the damaged stress extension layer, further to the surface damaged layer, and then continued to focus upward into the air to determine the thickness of the substrate surface damaged layer and the damaged stress extension layer. With the substrate surface as the zero point, the axial test range is that the Raman laser spot gradually moves upward from -100μm inside the substrate to 30μm above the substrate surface. Figure 3 (b) is the stress axial distribution diagram of 5 points tested on the top, bottom, left and right of the substrate. The 5 points on the substrate show the same trend, and there is only a difference in the maximum negative stress at the surface damage.
[0096] Figure 3 In (b), the stress fluctuates up and down along the horizontal line from -100μm in the substrate to -30μm, indicating that the internal stress is uniform; when the laser spot is focused on the damaged stress extension layer, the stress curve begins to show a downward trend at -30μm, and the downward trend of stress gradually increases. When it approaches the zero point on the substrate surface, it reaches the negative stress maximum value, which is the stress value of the surface damaged layer; finally, the laser spot continues to move upward and gradually leaves the substrate surface into the air, and the stress shows a rapid rise to chaotic fluctuations. Therefore, the thickness of the surface damaged layer and the damaged stress extension layer of the substrate can be determined according to the axial test results of the substrate, thereby distinguishing the stress in the substrate into surface stress and internal stress, which provides a theoretical basis for the subsequent quantitative test of the surface stress and internal stress in the substrate.
[0097] Example 4 Quantitative Testing of Stress in the Substrate
[0098] During the PVT crystal growth process, silicon carbide is affected by temperature gradient changes and the intrusion of inclusions, resulting in residual stress in the crystal. Different from the surface processing stress, the internal stress is located at a certain depth from the surface, reflecting the thermal stress and residual stress of crystal growth. In addition, silicon carbide undergoes a large amount of external mechanical stress in the process of preparing the substrate from the crystal through a series of processing, and it is difficult to ensure that the surface is completely horizontal, that is, there is a certain degree of curvature on the surface of the substrate. According to the measurement method of the curvature of the substrate surface obtained by Raman testing in Example 2, this embodiment, combined with the physical properties of silicon carbide, involves a method for quantitatively characterizing its internal stress that is not affected by surface curvature.
[0099] According to the physical property of silicon carbide being light-transmissive, the method of using Raman to quantitatively characterize the internal stress of the substrate is divided into equal-spacing focusing test and equal-focusing plane test, as follows:
[0100] 1. Equally spaced focus test
[0101] In the equidistant focusing test mode, the focal depth (d) of the Raman laser focused on the inside of the substrate at different test points remains unchanged. First, the penetration depth (Dp) of the Raman laser is calculated according to the following formula:
[0102]
[0103] In the above formula, Dp is the penetration depth of Raman excitation in the sample, α is the absorption coefficient, λ is the laser wavelength, and k is the extinction coefficient. The specific value of the penetration depth (Dp) is calculated according to the above formula, and a suitable focusing depth (d) is selected. The requirement that needs to be met is that the penetration depth (Dp) is greater than the focusing depth (d), and since the test is for internal stress, the focusing depth d needs to be greater than the thickness of the surface damage layer and the damage stress extension layer tested in Example 3.
[0104] The Raman laser spot diameter (D) is then calculated according to the following formula:
[0105] Where λ is the laser wavelength and Na is the numerical aperture of the device.
[0106] The spot diameter (D) is the short axis diameter of the laser spot. The larger the value, the stronger the peak intensity of Raman at each test position, and the more impurity peaks there are, which affects the detection accuracy of Raman. When λ is determined, if the value of Na is large, the peak intensity is very weak, which will also affect the Raman detection accuracy. Therefore, it is necessary to select appropriate λ and Na to improve the accuracy of the test method.
[0107] According to the material properties of silicon carbide, the peak intensity reaches the highest when the laser is focused on the substrate surface, such as Figure 2 As shown, the automatic focusing function of the Raman tester can be used to focus the laser on the substrate surface, and then according to the focusing depth (d) determined as above, an equidistant focusing test can be performed on different test points of the substrate, that is, the distance between the focusing plane and the substrate surface is always equal. This method is not affected by the bending and warping of the substrate surface, so that the obtained Raman peak intensity is always maintained at the axial maximum value of the test point. According to the stress quantitative testing method of Example 1, the in vivo stress test result diagram of the substrate is obtained.
[0108] 2. Equifocal plane test
[0109] Under the equal-focusing plane test mode, the focus depth (d) of the Raman laser spot focused on the inside of the substrate changes at different test points. The laser spot at different test points is focused on the same plane inside the substrate. The penetration depth (Dp) of the Raman laser is calculated according to the same formula as the equal-interval focusing test, and the appropriate focus depth (d) is selected in the same selection method.
[0110] Since the focus planes in this test method are equal, combined with the characteristics of silicon carbide, when the laser is focused on the substrate surface, the peak intensity reaches the highest and the signal gradually decays with the increase of the focus depth. And according to the effective signal-to-noise ratio tested by the Raman tester, it is found that the effective signal-to-noise ratio is inversely correlated with the Raman laser focus depth (d). Therefore, in this test method, the focus depth (d) at different test points needs to be combined with the curvature of the substrate to obtain the effective peak position offset through the stress quantitative test method of Example 1, thereby reducing the error of the in vivo stress test.
[0111] Through the above two testing methods of equal spacing focusing and equal focusing plane, the peak position offset inside the substrate is obtained respectively, and the internal stress distribution of the substrate is calculated. The difference between the internal stress values of the substrate calculated by the equal spacing focusing test and the equal focusing plane test is ≤0.2Mpa, and the peak position difference between the equal spacing focusing test and the equal focusing plane test is <0.0005cm -1 The above two methods can verify the accuracy of the quantitative detection method of the present application, and the accuracy of the test method can be further improved according to the setting of the focus depth and the spot diameter.
[0112] The internal stress includes the internal absolute stress and the internal relative stress, which is illustrated by taking 4H-SiC as an example:
[0113] The absolute stress in the body is calculated by subtracting the measured 4H-SiC peak position from the standard peak position to determine the simplified wave vector peak position, such as FTO (2 / 4). The absolute stress in the body is calculated as:
[0114] σabsolute=μ×(v 实际 -V FTO(2 / 4) ), σ is in MPa, v 实际 and V FTO(2 / 4) The unit is cm -1 , where v 实际 is the actual FTO(2 / 4) peak position at the substrate test point, V FTO(2 / 4) is the standard peak position of FTO (2 / 4) of the substrate;
[0115] The relative stress in the body is calculated by subtracting the measured values of the same simplified wave vector peak position at any two points in the SiC substrate surface, such as the FTO (2 / 4) peak position. The calculation formula for the relative stress in the body is:
[0116] σrelative=μ×(v (x1,y1) -V (x2,y2) ), σ is in MPa, v (x1,y1) and V (x2,y2) The unit is cm -1 , where v (x1,y1) is the actual FTO(2 / 4) peak position at the substrate test point, V (x2,y2)is the actual FTO (2 / 4) peak position of the substrate relative point. The relative stress value of the test point is calculated according to the above calculation formula. If the relative value of σ is positive, it means that the stress of the test point relative to the relative point is tensile stress. If the relative value of σ is negative, it means that the stress of the test point relative to the relative point is compressive stress.
[0117] Example 5 Quantitative Testing of Substrate Surface Stress
[0118] According to the axial test of Example 3, the thickness of the surface damage layer of the substrate is determined. Since the thickness of the surface damage layer of the substrate is less than the curvature of the substrate surface, the laser spot falls into the interior of the substrate in the equal focal plane test method, resulting in errors in the test results of the substrate surface stress. Therefore, the equal spacing focusing test method is mainly used in the quantitative test of the surface stress. In this test mode, the focal depth (d) of the Raman laser focused on the surface damage layer of the substrate at different test points remains unchanged.
[0119] First, the penetration depth (Dp) of the Raman laser and the spot diameter (D) of the Raman laser are calculated according to the same formula as in Example 4, and a suitable focusing depth (d) is selected. The requirements to be met are that the penetration depth (Dp) is greater than the focusing depth (d), and the Raman laser spot is located in the surface damage layer.
[0120] According to the above-determined focusing depth (d) and spot diameter (D), by debugging the parameters of the Raman tester, the laser is focused on the substrate surface using the automatic focusing function, so that the surface damage layer of the substrate introduced by processing falls within the range of the laser spot, thereby achieving equidistant focusing tests at different test points of the substrate, that is, the distance between the focusing plane and the substrate surface is always equal. This method is not affected by the bending and warping of the substrate surface, so that the obtained Raman peak intensity is always maintained at the axial maximum value of the test point. According to the stress quantitative testing method of Example 1, the surface stress test result of the substrate is obtained.
[0121] The method for quantitatively testing the surface stress and internal stress of the substrate in Example 4 and Example 5 can eliminate the influence of the bending and warping of the substrate surface, realize the quantitative testing of the surface stress and internal stress of the substrate, and improve the testing accuracy of the testing method; and can play a feedback role in the adjustment of the parameters of each process of crystal growth and / or substrate processing, thereby optimizing the various process parameters of the crystal growth process or the substrate processing process to prepare a high-quality substrate.
[0122] Example 6
[0123] This embodiment relates to a method for preparing a TaC coating having a through-type through hole, comprising the following steps:
[0124] (1) preparing a slurry: 25-40 parts of TaC powder, 5-8 parts of Ta2O5, 20-35 parts of a solvent, 15-25 parts of a cosolvent, 1-3 parts of an air entraining agent, 2-5 parts of a thickener, 5-15 parts of a straight-chain saturated aliphatic hydrocarbon and 1-3 parts of a carbon powder are mixed and stirred at 700-800 r / min for 2-3 hours to obtain a slurry containing TaC;
[0125] (2) Spraying the slurry onto a surface of a graphite substrate, heating to 60-80° C., maintaining for 2-4 hours to burst bubbles, and then drying at 180-220° C. for 8-12 hours; sintering at 700-900 mbar and 500-700° C. for 3-5 hours; then increasing the pressure to 1000-1100 mbar, increasing the temperature to 1600-1800° C., and sintering for 8-10 hours; then adjusting the pressure to 145-155 kPa, increasing the temperature to 2200-2400° C., sintering for 14-16 hours, and finally cooling to room temperature and normal pressure within 15-25 hours to obtain a TaC coating with through-holes.
[0126] Crucibles 1#-8# and comparative crucibles D1#-D3# were prepared according to the above preparation method, as follows:
[0127] Crucible 1#
[0128] (1) preparing a slurry: 32.7 parts of TaC powder, 6 parts of Ta2O5, 25 parts of ethanol, 20 parts of tetrahydrofuran, 1.5 parts of a saponin-type air entraining agent, 3.5 parts of cellulose ether, 10 parts of a straight-chain saturated aliphatic hydrocarbon and 1.3 parts of carbon powder were mixed, and stirred at 700 r / min for 2.5 h to obtain a slurry containing TaC;
[0129] (2) The slurry of step (1) is electrostatically sprayed onto the surface of the graphite substrate, the temperature is raised to 70°C, maintained for 3 hours to burst the bubbles, dried at 200°C for 10 hours, and then sintered: sintered at 800 mbar and 600°C for 4 hours; then the pressure is raised to 1000 mbar, the temperature is raised to 1700°C, and sintered for 9 hours; then the pressure is adjusted to 150 kPa, the temperature is raised to 2300°C, and sintered for 15 hours, and finally cooled to room temperature and normal pressure within 20 hours to obtain crucible 1#.
[0130] Crucible 2#
[0131] (1) preparing slurry: 25 parts of TaC powder, 5 parts of Ta2O5, 20 parts of ethanol, 15 parts of tetrahydrofuran, 1 part of saponin-type air entraining agent, 2 parts of cellulose ether, 5 parts of straight-chain saturated aliphatic hydrocarbon and 1 part of carbon powder were mixed, and stirred at 800 r / min for 2 h to obtain a slurry containing TaC;
[0132] (2) The slurry of step (1) is electrostatically sprayed onto the surface of the graphite substrate, the temperature is raised to 60°C, maintained for 4 hours to burst the bubbles, dried at 180°C for 12 hours, and then sintered: sintered at 700 mbar and 500°C for 5 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1600°C, and sintered for 10 hours; then the pressure is adjusted to 145 kPa, the temperature is increased to 2200°C, and sintered for 16 hours, and finally cooled to room temperature and normal pressure within 15 hours to obtain crucible 2#.
[0133] Crucible 3#
[0134] (1) preparing a slurry: 40 parts of TaC powder, 8 parts of Ta2O5, 35 parts of ethanol, 25 parts of tetrahydrofuran, 3 parts of saponin-type air entraining agent, 5 parts of cellulose ether, 15 parts of straight-chain saturated aliphatic hydrocarbon and 3 parts of carbon powder were mixed, and stirred at 700 r / min for 3 h to obtain a slurry containing TaC;
[0135] (2) The slurry of step (1) was electrostatically sprayed onto the surface of the graphite substrate, the temperature was raised to 80°C, maintained for 2 hours to burst the bubbles, dried at 220°C for 8 hours, and then sintered: sintered at 900 mbar and 700°C for 3 hours; then the pressure was raised to 1100 mbar, the temperature was raised to 1800°C, and sintered for 8 hours; then the pressure was adjusted to 155 kPa, the temperature was raised to 2400°C, and sintered for 14 hours, and finally cooled to room temperature and normal pressure within 25 hours to obtain crucible 3#.
[0136] Crucible 4#
[0137] The difference between this embodiment and crucible 1# is that in step (1), the raw materials are mixed and stirred at 700 r / min for 5 min, and the other conditions are the same as those of crucible 1#, to obtain TaC coating 4#.
[0138] Crucible 5#
[0139] The difference between this embodiment and crucible 1# is that in step (2), the slurry of step (1) is electrostatically sprayed onto the surface of the graphite substrate, the temperature is raised to 200°C, maintained for 13 hours to burst the bubbles and dried, and then sintered. The other conditions are the same as those of crucible 1#, and crucible 5# is obtained.
[0140] Crucible 6#
[0141] The difference between this embodiment and crucible 1# is that in step (2), the sintering is as follows: sintering at 400 mbar and 400°C for 4 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1700°C, and sintering is performed for 9 hours; then the pressure is adjusted to 150 kPa, the temperature is increased to 2300°C, and sintering is performed for 15 hours, and finally the temperature is lowered to room temperature and normal pressure within 20 hours. The remaining conditions are the same as those of crucible 1#, so that crucible 6# is obtained.
[0142] Crucible 7#
[0143] The difference between this embodiment and crucible 1# is that in step (2), the sintering is as follows: sintering at 800 mbar and 600°C for 4 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1200°C, and sintering is performed for 9 hours; then the pressure is adjusted to 150 kPa, the temperature is increased to 2300°C, and sintering is performed for 15 hours, and finally the temperature is lowered to room temperature and normal pressure within 20 hours. The remaining conditions are the same as those of crucible 1#, so that crucible 7# is obtained.
[0144] Crucible 8#
[0145] The difference between this embodiment and crucible 1# is that in step (2), the sintering is as follows: sintering at 800 mbar and 600°C for 4 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1700°C, and sintering is performed for 9 hours; then the pressure is adjusted to 120 kPa, the temperature is increased to 2500°C, and sintering is performed for 15 hours, and finally the temperature is lowered to room temperature and normal pressure within 20 hours. The remaining conditions are the same as those of crucible 1#, so that crucible 8# is obtained.
[0146] Comparison crucible D1#
[0147] Compared with crucible 1#, this comparative example adopts CVD method to prepare TaC coating, specifically:
[0148] The graphite substrate was placed in a chemical vapor deposition furnace and evacuated to below 50 Pa. The temperature was then raised to 1200°C, and a mixed gas consisting of ethane, TaCl5, H2 and carrier gas argon was introduced. The mixed gas maintained a stable flow rate into the deposition furnace, and the furnace pressure was maintained at 5000 Pa. The molar ratio of TaCl5 and ethane gas was first controlled at 1.2:1 to form a transition layer with a thickness of 50 μm; then the molar ratio of TaCl5 and ethane gas was controlled to 3:1 to form a TaC coating with a thickness of 60 μm, and a comparative crucible D1# was obtained.
[0149] Compare Crucible D2#
[0150] Compared with crucible 1#, the raw materials in the slurry of step (1) are different: BYK defoamer is used to replace the saponin air-entraining agent, and the other conditions are the same as those of crucible 1#, that is, comparative crucible D2# is prepared.
[0151] Compare Crucible D3#
[0152] Compared with crucible 1#, the raw materials in the slurry of step (1) are different: TaCl5 is used instead of Ta2O5, and the other conditions are the same as those of crucible 1#, that is, comparative crucible D3# is prepared.
[0153] The cross-sectional SEM test and EDS energy spectrum analysis were performed on the crucibles 1#-8# and the comparative crucibles D1#-D3# prepared above. Figure 4 It can be seen that Figure 4 (a) is the microscopic morphology of a TaC coating with through-holes, with holes of similar shape and size evenly distributed on its surface; Figure 4 (b) is the bubble morphology taken during the preparation of the TaC coating, in which it is clearly seen that the bubble size is uniform, so that the TaC coating with through-hole morphology is prepared, and its through-holes are also evenly distributed; Figure 4 (c) The coating is polished until the base graphite is exposed, and holes are still visible at this time, thus proving that the formed holes are through holes; Figure 4 (d) shows the SEM and EDS mapping of the coating demo cross section. The distribution of TaC and the penetration of the holes can be clearly seen in this image, and it is confirmed to be a Ta-containing coating through EDS. Figure 5 It can be seen that the TaC grains of the TaC coating grow in an oriented manner along the
[200] and
[220] directions. The thickness of the formed TaC coating, the average pore size and density of the through-holes in the TaC coating, and the size of the TaC grains were tested. The test results are shown in Table 1;
[0154] Table 1
[0155]
[0156] The crucibles 1#-8# and the comparative crucibles D1#-D3# prepared above were subjected to high temperature erosion and thermochemical erosion experiments to simulate the growth environment of the third generation semiconductor SiC crystal using the PVT method. The crucibles 1#-8# and the comparative crucibles D1#-D3# were kept at 2300°C and eroded in SiC atmosphere for 100 hours. The test results are shown in Table 2:
[0157] Table 2
[0158] sample Weight before experiment (g) Weight after the experiment (g) Erosion weight loss rate (%) Crucible 1# 753 702 6.8 Crucible 2# 714 639 10.5 Crucible 3# 742 701 5.5 Crucible 4# 747 714 4.4 Crucible 5# 760 721 5.1 Crucible 6# 741 708 4.5 Crucible 7# 755 716 5.2 Crucible 8# 749 698 6.8 Comparison crucible D1# 797 769 3.5 Compare Crucible D2# 761 707 4.1 Compare Crucible D3# 759 704 6.5
[0159] In Table 2, erosion weight loss rate = [(weight before experiment - weight after experiment) / weight before experiment] × 100%. The above high temperature erosion and thermochemical erosion experiments prove that the TaC coating of this embodiment can improve the protection performance of the graphite substrate, extend the tolerance and corrosion resistance of the TaC coating, and thus extend the service life of the crucible.
[0160] Example 7
[0161] This embodiment relates to a method for preparing a SiC single crystal, comprising the following steps:
[0162] (1) Adding silicon carbide powder into a crucible;
[0163] (2) Evacuate the furnace to 10 -6mbar, and then introduce high-purity inert gas to 300-500mbar, repeat this process 2-3 times, and finally evacuate the furnace to 10 -6 Below mbar;
[0164] (3) introducing high-purity inert gas into the furnace body, raising the pressure to 10-100 mbar within 1-3 hours, and continuously introducing high-purity inert gas and maintaining the pressure constant;
[0165] (4) Crystal growth stage: While maintaining the pressure unchanged, the temperature inside the furnace is raised to the crystal growth temperature of 2200K-2800K within 3-5 hours, and the growth time is 30-150 hours;
[0166] (5) After the single crystal growth is completed, open the furnace body and take out the graphite crucible to obtain the SiC single crystal.
[0167] Add equal amounts of silicon carbide powder to crucibles 1#-3# and comparative crucibles D1#-D3# prepared in Example 6, respectively; evacuate the furnace to 10 -6 mbar, and then introduce high-purity inert gas to 300 mbar. Repeat this process 3 times and finally evacuate the furnace to 10 -6 mbar or less; introduce high-purity inert gas into the furnace body, raise the pressure to 20mbar within 1 hour, continue to introduce high-purity inert gas and keep the pressure constant; crystal growth stage: while keeping the pressure constant, raise the temperature in the furnace body to the single crystal growth temperature of 2300K within 3 hours, and the growth time is 80 hours; after the single crystal growth is completed, open the furnace body, take out the graphite crucible, and obtain SiC single crystal crystals 1#-3# and comparison SiC single crystal crystals D1#-D3# respectively. The test method of Example 1-4 is used to perform radial and axial stress tests on the SiC single crystal crystals. Since the thickness of the SiC single crystal crystal is relatively thick, the SiC single crystal crystal can be sliced, and each SiC substrate is subjected to an in-vivo stress test, so that the difference in axial stress of the SiC single crystal crystal and the difference in radial stress of the SiC single crystal at different axial positions can be known. The test results are shown in Table 3 below:
[0168] Table 3
[0169] sample Radial stress (MPa) Axial stress (MPa) △S8(MPa) SiC single crystal crystal 1# -3.1~3.6 -1.3~1.7 0~1.1 SiC single crystal crystal 2# -7.8~8.0 -8.0~7.5 0~6.3 SiC single crystal crystal 3# -8.0~7.9 -7.6~7.8 0~10.0 Comparison of SiC single crystal D1# -15.0~15.5 -13.7~14.5 0~15.4 Comparison of SiC single crystal D2# -12.6~13.1 -10.2~12.3 0~13.7 Comparison of SiC single crystal D3# -7.4~11.8 -6.6~10.4 0~11.2
[0170] Example 8
[0171] This embodiment relates to the preparation of a SiC substrate, comprising the following steps:
[0172] (1) cutting the SiC single crystal and slicing it at a cutting speed of 0.005 mm / s to obtain a cut wafer;
[0173] (2) The cut wafers were passed through a main disk with a rotation speed of 75 r / min, using W10 diamond powder and a load of 0.3 kg / cm 2 Grinding to obtain a ground wafer;
[0174] (3) The ground wafer was passed through a main disk with a rotation speed of 80 r / min, using diamond powder with a particle size of W0.5 and a load of 0.5 kg / cm 2 Mechanical polishing and main disk speed 50r / min, ceramic disk speed 35r / min, chemical mechanical polishing liquid as polishing material, polishing pressure 0.15kg / cm 2 The SiC substrate was obtained after chemical polishing.
[0175] The SiC single crystal crystals 1#-3# prepared in Example 7 were subjected to the above steps of cutting, grinding, mechanical polishing and chemical mechanical polishing to obtain SiC substrates 1#-3#, and the SiC single crystal crystal 1# was sliced at a cutting speed of 0.003 mm / s; grinding: main disk speed 69 r / min, W10 particle size diamond powder, load 0.35 kg / cm 2 The ground wafer was passed through a main disk at a speed of 49 r / min, using W0.5 powder size diamond powder and a load of 0.5 kg / cm 2 Mechanical polishing and main disk speed 50r / min, ceramic disk speed 37r / min, chemical mechanical polishing liquid as polishing material, polishing pressure 0.18kg / cm 2 Chemical polishing was performed to obtain SiC substrate 4#, and the above SiC substrates 1#-4# were tested using the methods of Examples 1-5, and the results are shown in Tables 4 and 5. It can be seen from Tables 4 and 5 that the stress of the first surface layer and the second surface layer is basically the same, and the stress distribution of the middle layer is more uniform.
[0176] Table 4
[0177]
[0178] Table 5
[0179]
[0180] The stress values in Tables 3-5 all refer to relative stress values. In this application, the positive and negative values in the stress values represent whether the substrate is subjected to tensile stress or compressive stress. The △S1 and △S2 values in Table 4 are the results obtained by numerical calculation using relative stress. When absolute stress is used to characterize △S1 and △S2, the requirements of -15MPa≤△S1≤10MPa, -15MPa≤△S2≤10MPa can be met. In the prior art, when describing and evaluating the stress state of a substrate, the maximum value minus the minimum value in the above stress values is often used to obtain the difference to reflect the stress state of the substrate. For example, the axial stress of the first surface layer of SiC substrate 1# is -5.2-7.8. When the axial stress of the first surface layer of SiC substrate 1# is generally expressed in this field, it can also be described as a stress value of 13MPa.
[0181] The data in the above Tables 3-5 are only the SiC substrates and SiC crystals prepared by crucibles 1#-3# prepared in Example 6 and comparison crucibles D1#-D3#. When the same crystal growth and processing methods in Examples 7 and 8 are adopted and crucibles 4#-8# are used to prepare SiC crystals and SiC substrates, and when the parameters of the crystals and substrates in Tables 3-5 are characterized by absolute stress, the crystals can meet the requirements of axial absolute stress of -10MPa~10MPa, axial relative stress of -8MPa~8MPa; radial absolute stress of -10MPa~10MPa, radial relative stress of -8MPa~8MPa at any horizontal plane of the crystal; 0MPa≤△S8≤10MPa.
[0182] The substrate can satisfy -15MPa≤△S1≤10MPa, -15MPa≤△S2≤10MPa; -5MPa≤Smax3-Smax1≤5MPa; the radial absolute stress of the SiC substrate in the first surface layer is -15MPa~15MPa, and the radial relative stress is -15MPa~14.5MPa; the radial absolute stress of the SiC substrate in the second surface layer is -15MPa~15MPa, and the radial relative stress is -15MPa~14.5MPa; the radial absolute stress of the SiC substrate in the intermediate layer is -10MPa~10MPa, and the radial relative stress is -15MPa~14.5MPa. The stress is -8MPa~8MPa; -5MPa≤△S3≤5MPa, -5MPa≤△S4≤5MPa, -5MPa≤Smin3-Smin1≤5MPa; the axial stress of the SiC substrate in the first surface layer is -10MPa~10MPa, the axial stress of the SiC substrate in the middle layer is -10MPa~10MPa, and the axial stress of the SiC substrate in the second surface layer is -10MPa~10MPa; 0MPa≤△S5≤15MPa, 0MPa≤△S6≤10MPa, 0MPa≤△S7≤15MPa.
[0183] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A SiC substrate with uniform stress distribution in three dimensions, characterized in that: The thickness of the SiC substrate is not less than 100 μm, and the SiC substrate includes a first main surface and a second main surface, the area of the first main surface facing the second main surface at 10 nm to 30 μm is a first surface layer, the area of the second main surface facing the first main surface at 10 nm to 30 μm is a second surface layer, and the first surface layer and the second surface layer are between the intermediate layer; On the same axis, at any plane parallel to the first main surface or the second main surface, Smax1 represents the absolute maximum value of radial stress in the first surface layer, Smax2 represents the absolute maximum value of radial stress in the middle layer, Smax3 represents the absolute maximum value of radial stress in the second surface layer, △S1=Smax2-Smax1, △S2=Smax2-Smax3, -15MPa≤△S1≤10MPa, -15MPa≤△S2≤10MPa.
2. The SiC substrate according to claim 1, characterized in that At any plane in the first surface layer parallel to the first main surface, the radial stress of the SiC substrate is -15 MPa to 15 MPa; At any plane parallel to the second main surface in the second surface layer, the radial stress of the SiC substrate is -15 MPa to 15 MPa; At any plane in the intermediate layer parallel to the first main surface or the second main surface, the radial stress of the SiC substrate is -10 MPa to 10 MPa; The SiC substrate has a diameter of 150 mm or more. Preferably, -5MPa≤Smax3-Smax1≤5MPa.
3. The SiC substrate according to claim 1, characterized in that The radial stress includes radial absolute stress and radial relative stress; At any plane parallel to the first main surface in the first surface layer, the radial absolute stress of the SiC substrate is -15 MPa to 15 MPa, and the radial relative stress of the SiC substrate is -15 MPa to 14.5 MPa; At any plane parallel to the second main surface in the second surface layer, the radial absolute stress of the SiC substrate is -15 MPa to 15 MPa, and the radial relative stress of the SiC substrate is -15 MPa to 14.5 MPa; At any plane in the intermediate layer parallel to the first main surface or the second main surface, the radial absolute stress of the SiC substrate is -10 MPa to 10 MPa, and the radial relative stress of the SiC substrate is -8 MPa to 8 MPa.
4. The SiC substrate according to claim 1, characterized in that On the same axis, at any plane parallel to the first main surface or the second main surface, Smin1 represents the minimum absolute value of radial stress in the first surface layer, Smin2 represents the minimum absolute value of radial stress in the middle layer, Smin3 represents the minimum absolute value of radial stress in the second surface layer, △S3=Smin2-Smin1, △S4=Smin2-Smin3, -5MPa≤△S3≤5MPa, -5MPa≤△S4≤5MPa; Preferably, -5MPa≤Smin3-Smin1≤5MPa.
5. The SiC substrate according to claim 1, characterized in that An axial test is performed by extending vertically into the SiC substrate from any point on the first main surface, and the axial stress of the SiC substrate in the first surface layer is -10MPa to 10MPa, the axial stress of the SiC substrate in the middle layer is -10MPa to 10MPa, and the axial stress of the SiC substrate in the second surface layer is -10MPa to 10MPa.
6. The SiC substrate according to claim 1, characterized in that An axial test is performed vertically from any point of the first main surface into the SiC substrate, S1 is recorded as the maximum axial stress in the first surface layer, S2 is recorded as the minimum axial stress in the first surface layer, △S5=S1-S2, 0MPa≤△S5≤15MPa; S3 is recorded as the maximum axial stress in the middle layer, S4 is recorded as the minimum axial stress in the middle layer, △S6 = S3-S4, 0MPa≤△S6≤10MPa; S5 is recorded as the maximum axial stress in the second surface layer, S6 is recorded as the minimum axial stress in the second surface layer, △S7=S5-S6, 0MPa≤△S7≤15MPa.
7. A SiC crystal with uniform stress distribution in three dimensions, characterized in that: The thickness of the SiC crystal is not less than 0.35 mm, the SiC crystal includes an upper surface and a lower surface, and in the region from the upper surface to the lower surface, the radial stress at any horizontal plane is -10 MPa to 10 MPa; Preferably, the diameter of the SiC crystal is greater than 150 mm.
8. The SiC crystal according to claim 7, characterized in that: Extending downward from any point on the upper surface of the SiC crystal to perform an axial test, the axial stress of the SiC crystal is -10MPa to 10MPa; Preferably, the axial stress includes axial absolute stress and axial relative stress; An axial test is performed by extending downward from any point on the upper surface of the SiC crystal. The axial absolute stress of the SiC crystal is -10 MPa to 10 MPa, and the axial relative stress of the SiC crystal is -8 MPa to 8 MPa.
9. The SiC crystal according to claim 7, characterized in that: The radial stress includes radial absolute stress and radial relative stress; In the region from the upper surface to the lower surface, the radial absolute stress at any horizontal plane of the SiC crystal is -10 MPa to 10 MPa, and the radial relative stress at any horizontal plane of the SiC crystal is -8 MPa to 8 MPa.
10. The SiC crystal according to claim 7, characterized in that: An axial test is performed by extending downward from any point on the upper surface of the SiC crystal, S7 is recorded as the maximum axial stress of the SiC crystal, S8 is recorded as the minimum axial stress of the SiC crystal, △S8=S7-S8, 0MPa≤△S8≤10MPa.
Citation Information
Patent Citations
Processes and apparatus for preparing heterostructures with reduced strain by radial compression
CN108336013A
Silicon carbide crystal and preparation method thereof
CN110129885A
Silicon carbide substrate
CN111433394A
Treatment method of crucible for growth of low-stress silicon carbide single crystals and crystal growth method
CN113265706A
Silicon carbide crystal, seed crystal and substrate
CN115652432A
